Ten-Year Stability of an Insomnia Sleeper Phenotype and Its Association With Chronic Conditions - Lee, Soomi; Smith, Claire E; Wallace, Meredith L; Buxton, Orfeu M; Almeida, David M; Patel, Sanjay R; Andel, Ross (Psychosomatic medicine, 2024)
OBJECTIVE: To identify distinct sleep health phenotypes in adults, examine transitions in sleep health phenotypes over time, and subsequently relate these to the risk of chronic conditions. METHODS: A national sample of adults from the Midlife in the United States study ( N = 3683) provided longitudinal data with two time points (T1: 2004-2006, T2: 2013-2017). Participants self-reported on sleep health (regularity, satisfaction, alertness, efficiency, duration) and the number and type of chronic conditions. Covariates included age, sex, race, education, education, partnered status, number of children, work status, smoking, alcohol, and physical activity. RESULTS: Latent transition analysis identified four sleep health phenotypes across both time points: good sleepers, insomnia sleepers, weekend catch-up sleepers, and nappers. Between T1 and T2, the majority (77%) maintained their phenotype, with the nappers and insomnia sleepers being the most stable. In fully adjusted models with good sleepers at both time points as the reference, being an insomnia sleeper at either time point was related to having an increased number of total chronic conditions by 28%-81% at T2, adjusting for T1 conditions. Insomnia sleepers at both time points were at 72%-188% higher risk for cardiovascular disease, diabetes, depression, and frailty. Being a napper at any time point related to increased risks for diabetes, cancer, and frailty. Being a weekend catch-up sleeper was not associated with chronic conditions. Those with lower education and unemployed were more likely to be insomnia sleepers; older adults and retirees were more likely to be nappers. CONCLUSION: Findings indicate a heightened risk of chronic conditions involved in suboptimal sleep health phenotypes, mainly insomnia sleepers.
Keywords: fenotyp; Male; Phenotype; longitudinální studie; chronická nemoc; Sleep Initiation and Maintenance Disorders; Adult; Aged; dospělí; mužské pohlaví; senioři; Chronic Disease; poruchy iniciace a udržování spánku; lidé; United States; ženské pohlaví; Humans; Longitudinal Studies; Spojené státy americké; Female; lidé středního věku; Middle Aged